Public acceptance of hydrogen buses through policy instrument: Local government perceptions in Changwon city - Lee, Youhyun; Jung, Jaehyung; Song, Hyojin (International Journal of Hydrogen Energy, 2023)
The climate crisis demands a transition in transport policy. Eco-friendly mobility is rising as an alternative to combustion engine vehicles. This study has two critical novelties: First, hydrogen buses have rarely appeared in previous studies, despite their potential; this interdisciplinary research suggests a guideline for hydrogen driven transportation policy at a local level. Second, this study demonstrates priorities in actual policy implementation to promote public acceptance toward hydrogen buses Using the Analytic Hierarchy Process (AHP) for 35 policy practitioners in the local government, socio-political acceptance is deemed a priority, in order to implement the use of hydrogen buses. Additionally, supporting hydrogen infrastructure and facilitating and reinforcing greenhouse gas (GHG) mitigation regulation was prioritized along with the bus fee reduction with hydrogen buses. Carrot and stick style policy instruments were perceived as effective for promoting public acceptance. The results offer practical transport policy guidelines for other local governments in foreign countries.
Keywords: Combustion engines; Eco-friendly; Engine vehicle; Hydrogen bus; Local government; Policy implementations; Policy instruments; Public acceptance; Transport policy; Transportation policies; AHP; Hydrogen bus; Policy instrument; Public acceptance